El M-19 en el contexto de las guerrillas en Colombia - Luna Benítez, Mario (Sociedad y Economía, 2006)
This paper examines, with a critical approach, some arguments of political sociology in Colombia regarding the guerrillas, especially during the outset period. It restates the analytical features of armed groups and puts them in comparative relation to M-19. In this way the study of this group is placed in perspective and, as an alternative approach, it develops the relationship with different contexts of violence, marking continuities and discontinuities with the violence of 1950 ́s.